Practices of Tolerance: The Significance of Common Sense in Settings of Dense Coexistence - Heuser, Stefan (Religions, 2024)
Deriving from the growing cultural and religious diversity in Germany and the need for educational professionals to be able to deal with heterogeneous groups and communicate to children about how to coexist peacefully with others, this essay focuses on the relationship between common sense and tolerance, particularly in places of inescapable dense coexistence characterised by religious and cultural diversity. Using institutions of preschool and primary education as an example, the extent to which peaceful coexistence and conflict resolution is borne by common sense and supported by practices of tolerance is discussed. Subsequently, the significance of a common-sense approach to practices of tolerance for conceptualising ethical judgement in intercultural and inter-religious education is explored. The article closes with thoughts on the contribution of religious ethics to questions of human coexistence in highly dense and conflict-ridden contexts and briefly addresses aspects of Protestant social ethics.